PENGOBATAN TRADISIONAL DI MINANGKABAU - Masfalinda; Wela Yulia Fitri; Welda Wilis; Ahmad Taufik Hidayat (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2022)
Traditional medicine is a form of treatment method used by people since time immemorial. This knowledge is obtained through human experience and understanding of disease. Traditional medicine is in the form of potions, spells and some are in the form of amulets. Minangkabau society in ancient times also used traditional types of medicine. This can be known through ancient manuscripts found in several places in Minangkabau, such as in Surau, Rumah Gadang, Museum, and Library. This study was conducted to determine the form of traditional medicine in Minangkabau. The analysis was done descriptively. From this research, it is known that in Minangkabau there are several types of traditional medicine that can cure various diseases and even diseases that cannot be cured by hospital medicine can be cured by traditional medicine.